Additive manufacturing of cellular structures: Multiscale simulation and optimization. (9th June 2023) - Mergheim, Julia; Breuning, Christoph; Burkhardt, Christian; Hübner, Daniel; Köpf, Johannes; Herrnböck, Ludwig; Yang, Zerong; Körner, Carolin; Markl, Matthias; Steinmann, Paul; Stingl, Michael
Abstract: This paper introduces a multiscale and multi-purpose simulation framework to investigate selective beam melting processes for metallic cellular structures along the complete process chain, up to the topology optimization of components made of cellular materials. Process simulation methods on various length scales are introduced to analyze the relation of process strategies and resulting properties of the cellular materials, as e. g. warpage, residual stresses, material grain structure and surface roughness. Numerical homogenization methods are applied to investigate the influence of the grain structure and the topology of the cellular materials on their mechanical properties. Based on these process-dependent mechanical properties, a two-scale optimization of components made of cellular material is performed, aiming in particular on optimizing the buckling resistance of the structures. The interfaces between the different simulation tools are specified and illustrate the flexibility of the numerical framework. It is shown that consistent simulations of additive manufacturing of cellular materials – from the manufacturing process to the optimized component – provide important insights into process–structure interactions and enable tailored additive manufacturing processes.